Impact Of Financial Performance In Moderating Good Corporate Governance (GCG) With Profitability - Sri Rahayu Indah Azhari; Ira Nasriani; Safriadi Darmansyah; Zul kahfi; Idayanti Nursyamsi (Cita konsultindo, 2025)
This study examines the impact of Good Corporate Governance (GCG) on profitability, with the disclosure of financial performance serving as a moderating factor. The research sample comprises companies listed on the SRI-KEHATI index of the Indonesia Stock Exchange from 2021 to 2023. Data analysis was conducted using the Partial Least Square (PLS) technique. The findings reveal that while GCG has a positive influence on profitability, this effect is not statistically significant. However, when financial performance—particularly solvency—is introduced as a moderating variable, the relationship between GCG and profitability becomes both positive and significant. This suggests that stronger GCG practices, when reinforced by solid financial performance, notably enhance a company's profitability